Psychotherapeutic competence of nurses in a teaching and non-teaching hospital in Khonkaen Province, Thailand - Chintana Leelakraiwan
This study investigated the psychotherapeutic competencies of nurses working in medical and surgical wards of a general, non-teaching hospital and a teaching hospital in Khonkaen Province, Thailand. The nurses were tested in terms of 3 components of psychotherapeutic competencies, namely, knowledge, attitudes and skills, and the interrelationship among these components were studied. The relationship between psychotherapeutic competencies and the personal factors of age and length of professional experience and institutional factors such as type of hospital and area of specialization were also determined. A total of 59 registered nurses participated in this study. Standardized T-score, T-test, and correlation coefficients were computed. It was found that nurses in the teaching hospital and nurses in the non-teaching hospital are similarly distributed as to knowledge and attitudes components. However, with regards to the skill components, nurses in the teaching hospital showed average to the high level of competency whereas nurses in the non-teaching hospital had only moderate level of competency. No significant relationship was noted between nurses' scores on diffirent components of psychotherapeutic competency. Nurse's age and length of professional experience, and type of hospital were found to be significantly related to psychotherapeutic skill component, that is, the younger nurses with less experience and who worked in the teaching hospital have significantly higher scores on the skill component. The specialization of the ward areas was not significantly related to any psychotherapeutic component.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Nursing -- Practice